Analysis of ecological tourism in the European union: strategic guidelines for development - Mamotenko, Daria; But, Tetiana (Management and Entrepreneurship: Trends of Development, 2025)
The purpose of the article is to identify the key factors that determine the dynamics of ecotourism development in the European Union and to define strategic guidelines for the formation of an effective regional policy in this area. The methodological basis of the study is formed by general scientific and special methods of economic theory, in particular, statistical and information reports of the EU, IMARC Group and Booking.com on sustainable travel and ecotourism. Research results: The identified behavioural changes after COVID-19, regional and demographic differences in tourist preferences, as well as the level of information availability, allowed us to formulate strategic guidelines for the development of ecotourism in the EU. Factor analysis has confirmed that the success of ecotourism is significantly influenced by such factors as the availability of financial support, digitalisation of tourism services, certification of services, infrastructure accessibility and the level of environmental awareness. The proposed strategic guidelines can enhance the effectiveness of sustainable tourism policy through support for local businesses, personalised communication campaigns, and increased transparency of environmental standards. The results of the study can be used to develop regional roadmaps for ecotourism development, optimise the use of European programmes (Interreg, LIFE, Horizon Europe, ERDF), and intensify cluster development in the tourism sector. For Ukraine, which has suffered significant losses in ecotourism due to the war, the study provides a methodological basis for assessing the potential of regions, identifying priorities for post-war recovery and integration into the EU green space. The application of the factor approach will ensure the validity of management decisions in the field of sustainable tourism.JEL Classification: Q 1, Q 26, L 83, R 58.